THE INFLUENCE OF SPEEDING ON MOTORBIKE RIDERS ON MEDAN - Irmawati Irmawati; Meutia Nauly; Muhammad Ridwan Anas (Journal of Indonesia Road Safety, 2019)
Based on data and previous studies on the condition of the city of Medan. As a large city and the high accident rate. The purpose of this study is to study the effect of speed as a factor in the causes of traffic accidents. Which is related to the behavior of drivers in terrain cities, especially on national road sections with a specification's minimum 4/2 D. The location studied in six road sections that are considered to represent 14 road segments in accordance with the scope of the study area, namely the road (1) Jalan Industri, (2) Jalan Gagak Hitam, (3) Jalan Ngumban Surbakti, (4) Jalan Sisingamangaraja, (5) Jalan. Yos Sudarso, (6) Jalan A.H. Nasution. The analysis uses a t-test for a comparative test. Behavioral studies use a mixed design approach that is carried out in parallel, through FGD and on-line surveys (N = 200) using a scale that measures attitudes, beliefs, subjective norms of people around the driver, perceptions of the risk of speeding behavior and demographic questions. The results of the study show that there is an influence of the average speed of roads at the accident rate of national roads. The attitudes and beliefs of research participants tended to be opposed to 'speeding' behavior. Subjective norms of people around the driver as well as showed negative attitudes. Research participants also display high-impact perceptions of the likelihood of accidents caused by their 'speeding' behavior. Based on the regression analysis, it can be concluded that there is a meaningful relationship between participants' attitudes towards' speeding 'and subjective norms (attitudes and beliefs of the surrounding environment towards' speeding'. Berdasarkan data dan kajian sebelumnya mengenai kondisi kota Medan sebagai kota besar dan tingkat kecelakaan yang termasuk tinggi, maka tujuan dari penelitian ini adalah melakukan kajian pengaruh kecepatan sebagai faktor penyebab kecelakaan lalu lintas, yang terkait denganperilaku pengemudi di kota medan khususnya pada ruas jalan nasional dengan spesifikasi minimal 4/2 D. Lokasi yang diteliti merupakan 6 ruas jalan yang dianggap mewakili 14 ruas jalan sesuai dengan lingkup wilayah studi, yakni (1) Jalan Industri, (2) Jalan Gagak Hitam, (3) Jalan Ngumban Surbakti, (4) Jalan Sisingamangaraja, (5) Jalan. Yos sudarso, dan (6) Jalan A.H. Nasution. Analisis menggunakan t tes untuk uji banding. Kajian perilaku menggunakan pendekatan mixed design yang dilakukan secara paralel, melalui FGD dan survey on line (N=200) dengan survey on line menggunakan skala yang mengukur sikap, belief, norma subyektif dari orang-orang di sekitar pengendara, persepsi terhadap resiko perilaku speeding dan pertanyaan demografik. Hasil studi menunjukkan terdapat pengaruh kecepatan rata-rata ruas jalan terhadap tingkat kecelakaan ruas-ruas jalan nasional. Sikap dan belief partisipan penelitian cenderung negatif terhadap perilaku 'speeding', norma subyektif orang-orang di sekitar pengendara juga menunjukkan sikap yang negatif. partisipan penelitian juga menampilkan persepsi yang mengarh ke tingggi terhadap kemungkinan kecelakaan yang diakibatkan oleh perilaku 'speeding' yang mereka lakukan. Bedasarkan analisis regresi diperoleh kesimpulan bahwa ada hubugnan yang berarti antara sikap partisipan terhadap 'speeding' dengan norma subyektif (sikap dan belief dari lingkungan sekitar terhadap 'speeding'.